Too big to fail : the inside story of how Wall Street and Washington fought to save the financial system--and themselves - Sorkin, Andrew Ross (Penguin Books, 2010)
Presents a moment-by-moment account of the recent financial collapse that documents state efforts to prevent an economic disaster, offering insight into the pivotal consequences of decisions made throughout the past decade.